The Impact of Artificial Intelligence on the Rights of Illustrator - I Putu Angga Maysa Putra; Made Satyadharma Laksana; Rizkita Ayu Mutiarani; I Putu Raditya Sudwika (Journal of Digital Law and Policy, 2022)
In the era of the industrial revolution 4.0, more and more technologies are developing very quickly. With rapid developments experiencing breakthroughs including in the field of Artificial Intelligence, where computer technology was created to create systems that can match the work done by humans. Artificial Intelligence itself is widely used in various industries such as education, health, manufacturing, services, and products. Artificial Intelligence itself is a tool which can help humans in making an illustration work. The illustrator is a profession that focuses on the field of fine arts, which generally creates or provides two-dimensional based illustration images. The presence of Artificial Intelligence or AI raises new questions, whether this illustrator's career will be relevant for a long time. The results of the research show that illustrators must make the best use of Artificial Intelligence technology, not feeling threatened by this technology. This study uses mixed research methods (Mixed Methods). Where in this study combined quantitative and qualitative research methods in collecting data to obtain research results that were tested for truth. The existence of this research aims to find out what the impact of the influence of AI can create a work with only a collection of words.